PENGARUH PENCELUPAN TELUR TETAS ITIK HIBRIDA MENGGUNAKAN EKSTRAK DAUN SALAM SEBAGAI DESINFEKTAN ALAMI TERHADAP DAYA TETAS, MORTALITAS EMBRIO, DAN SALEABLE DUCK - Reynaldy Gunawan; Khaira Nova; RR Riyanti; Dian Septinova (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2021)
This study aimed to determine the effect of immersion of hybrid duck eggs using bay leaf extract with different concentrations on embryo mortality, hatchability, and saleable duck and to determine the best concentration in immersing hybrid duck eggs using bay leaf extract on embryo mortality, hatchability, and saleable duck. The research was carried out in May - June 2020, the manufacture of bay leaf extract was carried out at the Animal Production and Reproduction Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, and the hatching process was carried out in Gunung Mas Village, Teluk Betung Selatan District, Bandar Lampung City. This study used a completely randomized design (CRD) with four treatments, namely without dyeing the bay leaf extract (P0), dyeing with bay leaf extract with a concentration of 10% (P1), dyeing with bay leaf extract with a concentration of 20% (P2), dyeing with bay leaf extract. with concentration of 30% (P3). Each treatment was repeated 5 times with each experimental unit amounting to 5 hybrid duck eggs so that 100 eggs were used. The variables observed were embryo mortality, hatchability, and saleable duck. The results showed that immersion of hybrid duck eggs using bay leaf extract at concentrations of 10%, 20%, and 30% had no significant effect on embryo mortality, hatchability, and salable duck of hybrid duck and there was no the best bay leaf solution dosage to reduce embryo mortality, and increase hatchability and saleable duck of hybrid duck. Keywords : Bay leaf, Embryo mortality, Extract, Hatchability, Hybrid duck, Saleable duck